2019
DOI: 10.5897/ajar2019.14457
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous rhizobia strains: The silver bullet for enhanced biological nitrogen fixation and soybean (Glycine max (L.) Merr. ) yield under different soil conditions in South Kivu province, Democratic Republic of Congo

Abstract: Soybean is an important crop in the Democratic Republic of Congo, a country faced with high levels of war induced malnutrition but its productivity is limited by poor soil fertility coupled with low access to nitrogen mineral fertilizers. Commercial rhizobia strains introduced in 2010 failed to adapt and increase soybeans yields at desired level. We studied the performance of six indigenous rhizobia strains in enhancing soybean productivity compared to two commercial strains USDA110 and SEMIA5019. The study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Wasike et al (2009a, b) confirmed also that applying P could improve nodulation capacity of different soybean varieties. Differences in nodulation capacity can also be due to varietal effect, soil acidity level, and P concentration (Ndusha et al 2019). With better nodulation, BNF satisfies up 30-80% of plant N requirement (Erman et al 2009).…”
Section: Applying Dap Fertilizer Improves Nodulation and Bnf On Pea U...mentioning
confidence: 99%
“…Wasike et al (2009a, b) confirmed also that applying P could improve nodulation capacity of different soybean varieties. Differences in nodulation capacity can also be due to varietal effect, soil acidity level, and P concentration (Ndusha et al 2019). With better nodulation, BNF satisfies up 30-80% of plant N requirement (Erman et al 2009).…”
Section: Applying Dap Fertilizer Improves Nodulation and Bnf On Pea U...mentioning
confidence: 99%
“…In line with previous research that N element plays a very important role in the formation and growth of vegetative organs (stems, leaves and roots), so that increasing the availability of N will increase the area of plant leaves which affects its assimilation. The N fixation process produces N which is released from the nodules in the form of urea (allantoin and allantoic acid) which is then translocated to the leaves and used for chlorophyll biosynthesis [14].…”
Section: Leaf Areamentioning
confidence: 99%
“…On the other hand, indigenous rhizobia have been observed to be more effective in fixing N than the commercial inoculants which have been previously used in soybean (Musiyiwa et al, 2005;Thuita et al, 2012;Thilakarathna and Raizada, 2017). The study conducted by Ndusha et al (2019) demonstrated the outperformance of indigenous species of B. japonicum over the commercial strain Bradyrhizobium diazoefficiens USDA110 by increasing the yield of soybean by 68.7 and 70.8% under greenhouse and field conditions, respectively. Similarly, Chibeba et al (2017) observed effective nodulation of 85 indigenous soybean nodulating rhizobia isolates under greenhouse conditions, whereby 10 isolates performed better than the best commercial reference strain, B. diazoefficiens USDA 110.…”
Section: Effectiveness Of Indigenous Soybean Nodulating Rhizobiamentioning
confidence: 99%